Corporate Governance and Institutional Investors: Evidence from Malaysia - Abdul Wahab, Effiezal Aswadi; How, J.; Verhoeven, P. (Asian Academy of Manaagement and Penerbit Universiti Sains Malaysia, 2008)
In 2001, Malaysia undertook important corporate governance reforms, which saw theintegration of the Malaysian Code on Corporate Governance (MCCG) into KualaLumpur Stock Exchange (KLSE) Listing Rules and the establishment of the MinorityShareholder Watchdog Group (MSWG), which aims to enhance institutional investoractivism. Following this development, this study investigates the relationship betweencorporate governance and institutional ownership in Malaysia. Our panel analysis of 434firms listed on Bursa Malaysia during 1999–2002 finds that institutional ownership ispositively and significantly related to corporate governance. However, we find that therelationship becomes less positive after 2001, suggesting that the monitoring effects ofinstitutional ownership and corporate governance arise simultaneously andendogenously.